Epithelial architecture and signaling activity in the adult human esophagus - Grommisch, David; Eenjes, Evelien; Troost, Maeve L.; Genander, Maria (Frontiers in Cell and Developmental Biology, 2025)
Barrier epithelia function to shield the inside of our bodies from external stressors and pathogens. The esophageal epithelium is no exception, providing protection while at the same time transporting food to the stomach. Although many epithelial tissues are comparable between humans and mice, the human esophageal epithelium displays unique features in both progenitor cell organization and tissue architecture compared to the mouse. These differences have limited our understanding of the adult human esophagus, hindering the development of therapeutic strategies targeting human esophageal disease. Herein, we contrast the esophageal epithelial architecture and progenitor cell populations in mice and humans and discuss the role of a tentative human-specific progenitor cell population located in the submucosal gland ducts. Furthermore, we review current models available to study the human esophageal epithelium, focusing predominantly on adult primary organoids and epithelioids as well as the generation of human developmental esophageal epithelial cells from induced pluripotent stem cells. Finally, we discuss signaling activity implicated in maintaining normal human epithelial homeostasis, and how these pathways contribute to disease development. We aim to provide a comprehensive outlook on our current understanding of the human esophageal epithelium, while simultaneously highlighting unanswered questions in esophageal epithelial maintenance.